ҮСТИРТТЕГИ ОРТА ӘСИРДЕГИ ТУРМЫСТЫҢ ДӘРЕКЛЕРДЕ СӘЎЛЕЛЕНИЎИ - Қанаатов, Е.Е. (FAN va JAMIYAT, 2024)
The article describes the historical sources written about the peoples and peoples who lived in the Ustyurt desert in the Middle Ages and their way of life. Arabic-Persian sources also contain information about trade routes that crossed the Ustyurt desert. This information helps to understand the life in Ustyurt in the Middle Ages.